Contested Identities: How Ethnic and Religious Communities Perceive Multiculturalism in Southeast Sulawesi, Indonesia: , - Danial Danial; Hasbulloh Nadaraning; Faza Achsan Baihaqi; Nilam Nur Raya (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Indonesia’s commitment to diversity through Pancasila and Bhinneka Tunggal Ika provides a normative foundation for multiculturalism. However, ethnic and religious diversity continues to generate both social cohesion and contestation. Southeast Sulawesi, home to Tolaki, Muna, Buton, Bugis, Balinese, and other communities, offers a valuable setting for examining local understandings of multiculturalism. Objectives: This study explores how members of diverse ethnic and religious communities conceptualize multiculturalism, negotiate identities, and evaluate opportunities and challenges of coexistence. Methods: A qualitative study using interpretive phenomenological analysis was conducted. In-depth semi-structured interviews were carried out with 34 participants from diverse ethnic (Tolaki, Muna, Buton, Bugis, Balinese) and religious (Muslim, Christian, Hindu, and indigenous belief) backgrounds in Kendari and surrounding areas. Data were collected between November and December 2024 and analyzed thematically. Trustworthiness was enhanced through member checking, peer debriefing, and triangulation. Results: Three dimensions of contested multiculturalism emerged: definitional, evaluative, and normative contestation. Muslim-majority participants commonly emphasized ethnic diversity, national unity, and integration, whereas religious minorities highlighted pluralism and recognition. Migrant communities balanced cultural preservation with social integration, while indigenous groups expressed concerns regarding cultural marginalization and unequal power relations. Everyday multiculturalism was characterized by pragmatic coexistence despite persistent inequalities in recognition, resources, and political representation. Conclusion: Multiculturalism in Southeast Sulawesi remains a dynamic and contested process shaped by local histories, power relations, and lived experiences. Inclusive governance should address structural inequalities, strengthen intergroup dialogue, and promote meaningful recognition of marginalized communities. Keywords: ethnic identity, religious pluralism, identity negotiation, contested identities, intergroup relations.